2010
DOI: 10.1007/s11416-010-0142-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving antivirus accuracy with hypervisor assisted analysis

Abstract: Modern malware protection systems bring an especially difficult problem to antivirus scanners. Simple obfuscation methods can diminish the effectiveness of a scanner significantly, often times rendering them completely ineffective. This paper outlines the usage of a hypervisor based deobfuscation engine that greatly improves the effectiveness of existing scanning engines. We have modified the Ether malware analysis framework to add the following features to deobfuscation: section and header rebuilding and auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…These instructions provide the input to our algorithms. These instruction monitoring systems have been shown to be successful in a wide range of operations [26].…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…These instructions provide the input to our algorithms. These instruction monitoring systems have been shown to be successful in a wide range of operations [26].…”
Section: Data Collectionmentioning
confidence: 99%
“…At this time, the Ether portion of Xen is invoked and the malware is started. The sample is allowed to run for five minutes, which has been shown to be a sufficient time for execution [26].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [44], five minutes is sufficient duration for the execution monitoring. We doubled this execution time to capture the malware equipped with capability of carrying out time-out attacks.…”
Section: A Experimental Datasetmentioning
confidence: 99%
“…On the other hand, using dynamic data sources, the percentage of false positives that were packed is the same as the packed percentage of the training data, which would offer support for the kernels based on these data sources not being deceived by the packer. Although the dynamic traces of packed files will also have an unpacking "footprint", it has been shown that 5 minutes for a dynamic trace is enough time for a significant number of the instructions to represent the true behavior of the program [34]. A notable exception of static sources stumbling on programs that were packed is the disassembled data source (and the control flow graph which is based on the disassembled data source), but to get these data sources, we first had to unpack the binary.…”
Section: Observationsmentioning
confidence: 99%